Impact on Increasing Concentration in Indonesian Broiler Industry - Fitriani , Anna; Daryanto, Heny K.; Nurmalina, Rita; Susilowati, Sri Hery (International Journal of Poultry Science, 2014)
This study aims to analyze the market structure of the broiler industry in Indonesia using industry concentration ratio and barriers to entry and their impact on the level of competition in the broiler industry in Indonesia. Using secondary data time series from the Central Bureau of Statistics, CR4 calculations obtained in 2003 was 50.26 and in 2012 increased to 54.81, while the industry barriers to entry (MES) also tends to increase the value of which was in 2003 reached 0.126 while in 2012 be 0.137. The average output of the four largest companies reached 54.8 percent with barriers to entry at 0.137, so that it can be said that broiler industry market structure in Indonesia is an oligopoly with entry barriers are quite low. This means that the broiler industry in Indonesia has not been efficient. Conditions where large-scale enterprise and has integrated industry structure tends to cause high concentrated so vulnerable to unfair competition practices. The farmers through farmer organizations or professional organizations should actively conduct animal studies and research and active advocacy against government policies that may lead to unfair competition is detrimental to farmers.